PERBEDAAN DETERMINASI PROFITABILITAS PADA PERUSAHAAN BUMN PERIODE 2012-2016 - RAHMAWATI, FITRI, HARIYATI (Jurnal Akuntansi AKUNESA, 2018)
The performance of BUMN be a public concern, which is the profitthat has been earned. In 2017 there were 24 BUMN companies that suffered losses. Avoiding the wrong investment in the company that non profitable, it is necessary to analyze the ratios that affect profitability before investing. This study aims to determine the effect of liquidity, leverage, company size, cash turnover,and accounts receivable turnover on profitability in BUMN companiesin the 2012- 2016 period. In addition, it also aims to compare the determinants profitability of state-owned to the leadership of President Susilo Bambang Yudhoyono and Joko Widodo. The total sample of thestudy was 33 companies that matched the sampling criteria. The analysis tool used is SPSS 23 to process multiple linear regression analysis. The results of this study indicate that liquidity and cash turnover affect profitability while leverage, company size, and accounts receivable turnover not affect profitability. Keywords: Liquidity, Leverage, Company Size, cash turnover, and Accounts Receivable Turnover